Designing Snack-Based PMRI Problems to Support Elementary Students’ Understanding of Weight Measurement - Lisnani Lisnani; Adrianus Danang Setiawan; Gladys Sunzuma; Benidiktus Tanujaya; Zidni Naufal Fadhil (Universitas Papua, 2025)
Snacks, which are frequently encountered by elementary school students in their everyday lives, offer a meaningful context for learning about weight measurement. This study aims to design and develop weight measurement problems within the framework of the Indonesian Realistic Mathematics Education known as PMRI approach, with the goal of producing snack-based contextual tasks that are valid, practical, and instructionally effective. The research adopted a development-oriented design research methodology comprising two main phases: a preliminary phase and a formative evaluation phase. Participants included three students in the one-to-one stage, six students in the small-group stage, and seventeen students in the field test stage. Data were collected through document analysis, walkthroughs, classroom observations, interviews, and written assessments. The study yielded ten validated snack-based weight measurement problems for use in elementary mathematics classrooms. These products can support teachers in implementing contextual instruction on weight measurement and provide a basis for future research on the development of student worksheets grounded in contextual learning.